2003
DOI: 10.1056/nejmoa022171
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus for the Prevention of Allograft Rejection and Vasculopathy in Cardiac-Transplant Recipients

Abstract: Everolimus was more efficacious than azathioprine in reducing the severity and incidence of cardiac-allograft vasculopathy, suggesting that everolimus therapy may alleviate this serious problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
720
5
16

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 1,088 publications
(780 citation statements)
references
References 30 publications
32
720
5
16
Order By: Relevance
“…It has been reported that immunosuppressive treatment limited the progression of carotid arteriopathy in patients with SLE (3). The predominance of T cells in the arterial inflammatory infiltration observed in this patient and the histopathologic similarity to transplantassociated arteriopathy suggest that immunosuppressive treatment specifically targeting T lymphocytes or approaches aimed at interfering with peripheral T cell recruitment might be particularly effective in the prevention and treatment of this specific complication of SLE (17). 912 CONEN ET AL…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that immunosuppressive treatment limited the progression of carotid arteriopathy in patients with SLE (3). The predominance of T cells in the arterial inflammatory infiltration observed in this patient and the histopathologic similarity to transplantassociated arteriopathy suggest that immunosuppressive treatment specifically targeting T lymphocytes or approaches aimed at interfering with peripheral T cell recruitment might be particularly effective in the prevention and treatment of this specific complication of SLE (17). 912 CONEN ET AL…”
Section: Discussionmentioning
confidence: 82%
“…Other publications quoted the mortality from cardiovascular disease between 1.5 and 3% of the total number of patients alive at 1 year. In heart transplant recipients, the main causes for late secondary organ loss are vascular diseases and their complications (Abbasoglu et al, 1997;Pruthi et al, 2001;Rabkin et al, 2001;Eisen et al, 2003) It is true that classical cardiovascular risk factors like hypertension, obesity, diabetes mellitus and so on were also responsible for these incidences.…”
Section: Discussionmentioning
confidence: 99%
“…Other publications have given the mortality from CVD as between 1.5 and 3% of the total number of patients alive after one year. In heart transplant recipients, the main causes for late secondary organ loss are vascular diseases and their complications (Abbasoglu et al, 1997;Pruthi et al, 2001;Rabkin et al, 2001;Eisen et al, 2003). Classical cardiovascular risk factors such as hypertension, obesity, diabetes mellitus etc., were held responsible for these data.…”
Section: Discussionmentioning
confidence: 99%